Biochemical markers of recombinant human insulin‐like growth factor‐I (rhIGF‐I)/rhIGF binding protein‐3 (rhIGFBP‐3) misuse in athletes. Issue 11 (31st October 2013) - Guha, Nishan; Erotokritou‐Mulligan, Ioulietta; Nevitt, Simon P.; Francis, Michael; Bartlett, Christiaan; Cowan, David A.; Bassett, E. Eryl; Sönksen, Peter H.; Holt, Richard I. G.
Abstract : Insulin‐like growth factor‐I (IGF‐I) is reportedly misused by elite athletes, either alone or with growth hormone (GH). The GH‐2000 and GH‐2004 research groups previously developed a method for detecting GH misuse based on the GH‐sensitive markers IGF‐I and procollagen type III amino‐terminal propeptide (P‐III‐NP). Both markers increase in response to rhIGF‐I/rhIGF binding protein‐3 (rhIGFBP‐3) administration in recreational athletes. The aim of this pilot study was to assess the effect of rhIGF‐I/rhIGFBP‐3 administration on other serum markers of the GH‐IGF axis and on other bone and collagen markers. Twenty‐six female and 30 male recreational athletes were randomized to 28 days' treatment with placebo or rhIGF‐I/rhIGFBP‐3 complex, followed by 56 days' washout. GH‐IGF axis markers (IGFBP‐2, IGFBP‐3, acid‐labile subunit (ALS) and IGF‐II) and bone and collagen markers (procollagen type I carboxy‐terminal propeptide (PICP), type I collagen cross‐linked carboxy‐terminal telopeptide (ICTP) and osteocalcin) were measured using commercial immunoassays. In women in the high dose treatment group, mean IGF‐II decreased by 53% ( P =0.0028) on Day 21. Mean IGFBP‐2 increased by 119% ( P =0.0039) and mean ALS decreased by 40% ( P =0.0022) on Day 21. There were no significant changes in IGFBP‐3, osteocalcin, ICTP or PICP. In men in the high dose group, mean IGF‐II decreased by 51% on Day 21 ( P <0.0001). Mean IGFBP‐2 increased by 125% on Day 21 ( P =0.0003). There were no significant changes in IGFBP‐3, ALS, osteocalcin, ICTP or PICP. Serum IGFBP‐2 and IGF‐II may be useful markers of rhIGF‐I/rhIGFBP‐3 administration in both women and men while ALS may also be a useful marker in women; these markers are now undergoing further evaluation. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Preliminary investigations into serum markers of insulin‐like growth factor‐I (IGF‐I) misuse are presented. Serum IGFBP‐2, IGF‐II and ALS may be useful markers of rhIGF‐I/rhIGFBP‐3 administration and are undergoing further evaluation.